Pemberdayaan Masyarakat melalui Program Greenstart: Upaya Peningkatan Ketahanan Pangan dan Pencegahan Stunting di Desa Sekong - Firdaus, Dafiq Zulina; Sopiandini, Isvie Tresna; Senjaya, Syifa Zahra Malya; Nugeraha, Fathansah; Dzakhwan, Ardell Reynara; Rahayu, Ergiana; Pramudytha, Agiska; Ritonga, Arya Widura; Nurandini, Hanifah Anggit (Direktorat Pengembangan Masyarakat Agromaritim, Institut Pertanian Bogor, 2025)
The Greenstart Program is a community empowerment innovation that aims to improve food security and prevent stunting through the use of home gardens for growing highly nutritious vegetables. The activity was carried out in Sekong Village, Cimanuk District, Pandeglang Regency, involving 57 households as participants. The implementation methods included the distribution of spinach and kale seeds, technical assistance, and routine monitoring for four weeks. The results of the activities showed a high level of participation with the distribution of 220 polybags of seeds to households. The evaluation showed that 52 households understood the appropriate watering times, 34 households understood how to cultivate the vegetables, and 37 households successfully harvested vegetables for family consumption. The main obstacles faced were chicken pests (56.1%) and caterpillars (43.9%), as well as necrosis disease (35.1%). The program succeeded in increasing family food self-sufficiency and reducing vegetable shopping expenses, but it still requires ongoing assistance to optimize results.